2018
DOI: 10.1177/1533033818758108
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-30a Mediates Cell Migration and Invasion by Targeting Metadherin in Colorectal Cancer

Abstract: MicroRNAs play critical roles in the occurrence and progression in various cancers including colorectal cancer. Here, we found that microRNA-30a expression was significantly downregulated in colorectal cancer tissues compared to adjacent noncancerous tissues, and the suppression levels of microRNA-30a were significantly associated with tumor differentiation and lymph node metastasis. We also discovered that the expression level of microRNA-30a was inversely proportional to the invasive potential of several col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 32 publications
(66 reference statements)
0
13
0
Order By: Relevance
“…39,40 Although, for miR-17, miR-20a, miR-30a, and miR-92a previous studies have shown no significant relation between miRNA expression and stage. 20,41,42 miR-92b expression has not been related to stage before and Zhu et al found lower levels of miR-98 expression in patients with stage III-IV disease compared to patients with stage I-II disease. 43 Since there was no significant difference in miRNA expression between patients with stage I-III (32%) vs stage IV (66.7%) disease in the previous cohort (see Table 1), we considered it worthwhile testing this signature in a cohort consisting of only patients with stage IV disease, who are starting first-line palliative systemic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…39,40 Although, for miR-17, miR-20a, miR-30a, and miR-92a previous studies have shown no significant relation between miRNA expression and stage. 20,41,42 miR-92b expression has not been related to stage before and Zhu et al found lower levels of miR-98 expression in patients with stage III-IV disease compared to patients with stage I-II disease. 43 Since there was no significant difference in miRNA expression between patients with stage I-III (32%) vs stage IV (66.7%) disease in the previous cohort (see Table 1), we considered it worthwhile testing this signature in a cohort consisting of only patients with stage IV disease, who are starting first-line palliative systemic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that the expression of miR-30a was slightly, but statistically significantly higher in the blood of patients with colonic or rectal cancer and in stage II and III compared to controls. This is contradictory to the literature since many publications mention that miR-30a has an antimetastatic effect and expression was lower in patients with colorectal tumours (14)(15)(16)(17).…”
Section: Discussionmentioning
confidence: 60%
“…These biomarkers can be used for early diagnosis, individualized treatment and prognosis of colorectal cancer [36]. For example, hsa-mir-183-5p and hsa-mir-21-5p [37], hsa-mir-30a [38], hsa-mir-96 [39], hsa-mir-21 [40] for diagnosis of colorectal cancer. And hsa-mir-143 and hsa-mir-145 for prognosis of colorectal cancer [41].…”
Section: Discussionmentioning
confidence: 99%